Isolation and identification of dermatophytes fungi from under two year children in diaber location - Majid kadhim; Abbas al. hussainy (Al-Qadisiyah Journal of Pure Science, 2017)
This study has been done to insulate and diagnose the( Candida spp ) from babies under two years in the place of the baby nappy . To know exactly the existence attribution of these (Candida spp ) and to study their sensivitiy t o anti-funguses (Ltraconazol (LTZ ) , Fluconazole (FLZ ) , Amphtericin – B , Nystatin , Ketoconazol (KTZ) ) . This study has also included discerning the relasionship between the way of using the baby nappy and the possibility of being ill by dividing it into three patterns ( neutral , intermitted and nightly ) . On the other side , discerning the effect of the environmental factor represented by the baby habitation whether it is city or countryside .Then , the Uresis test has been used to separate it from the continents while the germ tube test is used to differ the white ovaries from others .The use of to prevent the growth of the contaminant bacteria and the diagnose of different kinds is depended upon the the instruments of testing (RapiD , Yeast, plus ,, Color , Guide ) . The results were analysied by using a statistical programme ( SPSS) 2007 in analyzing the data to study the effect of different factors to the tested features . The (ANOVA ) was used on (10,0 ) incorporeal level by the statistical programme ( Excel ) . When the incorporeal differences were compared with the averages by ( LSD) the results were that the tested anti-funguses had a fatal effect towards the all kinds of isolated yeasts in different degrees depending on the kind of yeasts . And it demonstrated a clear impact to the way of using the baby nappy and the habitation of the patient.